Rancang Bangun Prototipe Alat Pengering Singkong Otomatis Menggunakan Mikrokontroler Arduino Uno - Rohmani, Nailu Sofwatur; Munazilin, Akhlis; Lutfi, Ahmad (Jurnal Ilmu Komputer (JUIK), 2024)
This study aims to develop and test an automatic cassava dryer that can improve the efficiency and quality of the drying process. The research methodology includes the design and construction of equipment and performance testing through a series of experiments measuring humidity levels, drying time, and energy consumption. The results of the study indicate that the automatic cassava dryer can reduce drying time by up to 50% compared to conventional methods, thus providing more uniform and quality end results. The discussion in this article includes a technical analysis of the device, a comparison with traditional drying methods, and an economic and environmental assessment. The conclusion of this study is that the automatic cassava dryer is an improvement in the cassava drying process that is effective, efficient and has the potential to be applied on an industrial scale. This study aims to develop an efficient cassava dryer for micro, small, and medium enterprises (MSMEs). The main problems faced by MSMEs in cassava processing are inefficiency of time and cost and low product quality due to suboptimal drying methods. This dryer is designed using [type of technology] and [materials used] technology, with a focus on energy efficiency and drying speed. The test results show that this tool is able to reduce drying time by up to 50% compared to traditional methods, as well as improve the quality of dried cassava in terms of texture and color. This drying tool is expected to help MSMEs increase productivity and product quality, as well as open up opportunities for the development of other cassava processed products.